2016
DOI: 10.1016/j.tranon.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Serum Protein Signature for Pancreatic Cancer to Separate Cases from Controls in a Pancreatic Surveillance Cohort

Abstract: BACKGROUND: Pancreatic cancer (PC) surveillance is currently offered to individuals with a genetic predisposition to PC, but routinely used radiological screening modalities are not entirely reliable in detecting early-stage PC or its precursor lesions. We recently identified a discriminating PC biomarker signature in a sporadic patient cohort. In this study, we investigated if protein profiling can accurately distinguish PC from non-PC in a pancreatic surveillance cohort of genetically predisposed individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Slater et al [8, 9] reported promising results on the use of tumour markers, including micro-RNAs 196a and b, LCN2, and TIMP1. In a small pilot study, the application of proteomics allowed us to differentiate between malignant and benign lesions [10]. However, these findings should be confirmed in larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…Slater et al [8, 9] reported promising results on the use of tumour markers, including micro-RNAs 196a and b, LCN2, and TIMP1. In a small pilot study, the application of proteomics allowed us to differentiate between malignant and benign lesions [10]. However, these findings should be confirmed in larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although these screening modalities are generally able to detect PDAC; none of them have been implemented in daily practice so far due to poor consistency of results [32]. Most of pancreatic cancer metabolomics studies used sample size ranging from 40 to 100 while only a few numbers of studies used more than 500 samples [33][34][35], and insufficient sample size may result in unrepresentative and variable results. Furthermore, there shall be a tendency to recover for effective biomarkers after tumor resection for the post-operative monitoring.…”
Section: Ivyspringmentioning
confidence: 99%
“…Large surveillance studies have been conducted on high-risk cohorts with demonstrated survival benefits [ 18 ]. Potjer and colleagues examined performance of a serum-based proteomic panel for early detection in a high-risk cohort undergoing imaging-based surveillance for PDAC [ 46 ]. This study design is one way forward because it incorporates intended use of screening high-risk patients, as well as imaging.…”
Section: Biomarker Challengesmentioning
confidence: 99%